Determination of Atenolol and Trimetazidine in Pharmaceutical Tablets and Human Urine Using a High Performance Liquid Chromatography-Photo Diode Array Detection Method - Walaa El-Alfy; Omnia A. Ismaiel; Magda Y. El-Mammli; Abdalla Shalaby (International Journal of Analytical Chemistry)
A simple RP-HPLC-PDA method for determination of atenolol (ATN) and trimetazidine (TMZ) in human urine and tablets has been developed. Analytes were separated on a Caltrex BI column (125× 4.0 mm, 5 μm) with 25mM potassium dihydrogen phosphate pH 3.3, methanol, and acetonitrile mobile phases. The PDA detector was operated at 210 nm for TMZ and 225 nm for ATN and the flow rate was 1.0 mL/ min. Linearity was obtained over a concentration range of (1.0-100 μg/mL) for both analytes in standard solutions and the method was successfully applied for determination of target analytes in their pharmaceutical tablets. Excellent linearity was also obtained over concentration ranges of (0.25-25 μg/mL) and (0.5-25 μg/mL) in human urine for TMZ and ATN, respectively. A simple liquid-liquid extraction was applied for urine sample clean-up and a gradient method was used for chromatographic separation. The lower limit of quantitation (LOQ) was 0.99 and 0.60 μg/mL for ATN and TMZ, respectively. The limit of detection (LOD) was 0.30 and 0.18 μg/mL for ATN and TMZ, respectively. Inter- and intraday precision and accuracy for ATN were within ±1.89% in pure form and within ±2.85% in urine samples. Inter- and intraday precision and accuracy for TMZ were within ± 3.99% in pure form and within ± 3.19% in urine samples.